Risk Factors of Stunting in Children Under Five Years Old - Evi Irianti (Humanistic Network for Science and Technology (HNST), 2021)
Stunting has several risk factors that have been done by several researchers. Systematic literature review studies are conducted to determine the most powerful risk factors and directly influence the occurrence of stunting in toddlers or children under five years old. The study examined 27 papers with various research designs such as cross-sectional, case-control, cohort, and intervention using RCT. The study subjects in the paper studied an average of >40 samples as well as data analysis by the design of the research. The results of this study found that the strongest risk factors for stunting were food diversity and household food security, environmental sanitation and drinking water, early initiation of breastfeeding and breastfeeding, birth weight, and parenting and child health care. Handling stunting requires appropriate government policies for the community, especially improvement in the economic sector, in addition to the involvement of community participation in providing education and early detection stunting. It is necessary to further investigate the control of nutritional intake to modify these risk factors. Keywords: risk factors of stunting; food diversity; history of infectious diseases; environmental sanitation; parenting